Pengaruh Kepemimpinan dan Pengalaman Kerjaterhadap Etos Kerja Karyawan Pada Perusahaan Daerah Air Minum Kabupaten Banggai - La Saudin (Jurnal Online Manajemen ELPEI, 2021)
This study aims to find out whether the variables Leadership, and Work Experience partially and simultaneously have a positive and significant effect on Employee Work Ethics at Regional Water Supply Companies in Banggaid Regency and to analyze and find out whether of the two variables which has the dominant influence on Employee Work Ethics at Companies Banggai Regency Drinking Water Area. The samples in this study were 52 employees at the Banggai Regency Drinking Water Company. Library research methods (Library Research), namely research methods or techniques intended to obtain theories from books/literature and scientific writings that have a relationship with the discussion of this paper. For the research method using a field research method approach (Field Research), namely a research method carried out by making direct visits to research locations, namely the Regional Drinking Water Company in Banggai Regency. To obtain data by technique (Accidental Sampling) is a collection that is done through questionnaires and interviews. Documentation, namely data collection based on documents and other written reports that have something to do with this research and distributing questionnaires. And the data analysis method uses multiple linear regression analysis using SPSS. Based on the results of the study, it shows that partially the Leadership variable (X1), has a positive and significant influence on Employee Work Ethics (Y) at the Banggai Regional Drinking Water Company "partially the Work Experience variable (X2), has a positive and significant influence on Employee Work Ethics (Y) at the Company Banggai Regency Water Supply Area, the Work Experience variable (X2), has a dominant and significant influence on Employee Work Ethics (Y) at the Banggai Regency Water Supply Company.